(untitled) (Research, Society and Development, 2020)
Introduction: aging is a vital process that involves physiological, psychological and social aspects. Although there is a decline in many competences and skills in these aspects, the elderly can learn new languages, especially English, which is the most widely spoken worldwide. In this sense, the objective was to discuss the neurobiological, neuroplastic and psychopedagogical characteristics of senescence, in order to prove the elderly’s cognitive ability to learn new languages, specifically the English language. Methods: a narrative-type bibliographic review study was carried out of articles published in the last 10 years, whether in Portuguese or in other languages, using the bibliographic databases PubMed, SciELO, Lilacs, SCOPUS, Portal de Periódicos da Capes, SBU, Google Scholar and Psyinfo. The terms senescence, senility, human development, life cycle, elderly, old age, neurobiology, neuroplasticity, cognition, English language, psychopedagogy and the Boolean “e” were used as descriptors. Results and discussion: with the help of cerebral neuroplasticity, the brain of the elderly has the capacity to learn new languages, as long as there are adequate, positive and significant stimuli from their teachers. One of the characteristics of senility is the accumulation of life experiences, known as previous knowledge, which stimulate executive and cognitive functions, improving skills and abilities for learning the English language among the elderly. Being bilingual, these citizens, in addition to activating their nervous connections (making them increasingly complex), will be able to expand their knowledge and social relationships.